DAMPAK FILM SERIAL TERHADAP AKUISISI BAHASA ANAK - Liya Umaroh; Hetty Catur Ellyawati (Fakultas Bahasa dan Budaya Asing (FBBA), Universitas Muhammadiyah Semarang, 2016)
Childrens language skills already possessed since they were born in the world (nature). However, the development of language acquisition such as morphology, syntax, phonology, and pragmatics can be obtained from surrounding environment (nurture). Between heredity and environmental factors are closely related to the process of language acquisition. By now, many sources of childrens language acquisition demand all parents for accompanying their children's activities. One of the example is the accompaniment while they watched serial film. Various kinds of events can be enjoyed by children without considering the feasibility of the program. Therefore, this study focused on serial film entitled